The organizational basis of the orphans’ preparation to the different forms of the arrangement - Svetlana Saphonova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
In the article the problem of defining the orphans’ training for the transition to different forms of arrangement is described. This paper establishes that the legislative procedure of preparation is not spelled out, but only the practical experience has some changes. The article determines that in the preparation of orphans for various forms of arrangement we should take into account such indicators as age, past experience, the presence of family and individual characteristics.